Epidemiology of myasthenia gravis in the United States - Ye, Yun; Murdock, Dana Jorgensen; Chen, Chao; Liedtke, Wolfgang; Knox, Caitlin A. (Frontiers in Neurology, 2024)
Introduction Global studies of epidemiology of myasthenia gravis (MG) have pointed to increasing prevalence of this rare autoimmune disorder affecting the neuromuscular synapse; however, no new data for the USA were available for decades. We aimed to estimate the incidence rate and prevalence of MG in a large-scale insured US population. Methods We conducted a population-based retrospective cohort study to estimate the annual incidence and prevalence of MG cases in the USA during 2017. Using a previously validated algorithm, we identified cases of MG in two Truven Health MarketScan databases, which during 2017 included a sample of approximately 20 million commercially insured and Medicare recipients, plus 10 million Medicaid recipients. We report crude incidence and prevalence and calculated age-and sex-standardized estimates for the USA based on the 2017 American Community Survey. We estimated the number of adult cases during 2021 by extrapolating from the stratified estimates to the population size from the 2021 American Community Survey. Results From the US commercially/Medicare-insured cohort, we calculated an age-and sex-standardized incidence of 68.5 new cases per million person-years with an adjusted prevalence of 316.4 per million. Within the Medicaid-insured population, similar yet slightly lower numbers emerged: the adjusted incidence was 49.7 new cases per million person-years, and the adjusted prevalence rate was 203.7 cases per million. Given our results, we were able to estimate that there were approximately 82,715 US adults living with MG in 2021 (or an estimated 320.2 cases per million adults in the USA). We observed a strong effect of age and sex when stratifying the identified incidence rate and prevalence, with a pattern of female preponderance among the younger age brackets, a male preponderance for older cases in the commercially/Medicare-insured cohort, and the disease incidence and prevalence steadily increasing with age. Discussion Our updated US population-based estimates of MG epidemiology demonstrate an increase in the previously reported incidence and prevalence from over 20 years ago, in keeping with developments in westernized, industrialized countries. Notable findings of steadily increasing prevalence with age, driven by robust increases in elderly males, prompts questions for basic-translational research, therapeutics, and public health.